Catalogue of Egyptian, Near Eastern, Greek and Roman Antiquities - Anonymus, A. (1963)
Sotheby and Co. Sale February 24, 1964; No. 72 aB Siegelzylinder; 79 Assyrian bronze standing figure of a minor deity.